2019
DOI: 10.1161/circresaha.118.313795
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on Directions and Priorities for Future Preclinical Studies in Regenerative Medicine

Abstract: Disclosures DT holds a financial interest in Miromatrix, Inc. and is entitled to sales royalty through the University of Minnesota for products related to the research described in this paper. This relationship has been reviewed and managed by the University of Minnesota and the Texas Heart Institute in accordance with its conflict of interest policies. This does not alter the authors' adherence to the Circulation Research's policies on sharing data and materials. PF is the founder and CEO of Pharmahungary, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 132 publications
(122 reference statements)
0
27
0
Order By: Relevance
“…However, the more important consequence of this observation is that this process mimics aspects of cardiac remodeling. Extensive cardiac remodeling with global cardiac changing in gene expression occurs subsequently to myocardial infarction (MI) when repair processes occur [13][14][15]. Therefore, in the present study we investigated the expression of swiprosin-1 in cardiac tissue during subsequent cardiac remodeling.…”
Section: Introductionmentioning
confidence: 99%
“…However, the more important consequence of this observation is that this process mimics aspects of cardiac remodeling. Extensive cardiac remodeling with global cardiac changing in gene expression occurs subsequently to myocardial infarction (MI) when repair processes occur [13][14][15]. Therefore, in the present study we investigated the expression of swiprosin-1 in cardiac tissue during subsequent cardiac remodeling.…”
Section: Introductionmentioning
confidence: 99%
“…After two decades of intensive research in the field of cell therapy for heart disease, conclusive demonstration of therapeutic efficacy of the cells is still lacking, and a fundamental understanding of how cell therapy works is still elusive[1, 3, 4, 29-31]. This has led to discussions of changes in the field and search for new paradigms for future research.…”
Section: Discussionmentioning
confidence: 99%
“…This has led to discussions of changes in the field and search for new paradigms for future research. A paradigm of repeated dosing of cells has become one of the investigational priorities[4, 29, 32]. However, the lack of a reliable, repeatable cell delivery approach in preclinical studies using small animals hinders progress.…”
Section: Discussionmentioning
confidence: 99%
“…The biomechanical properties of naturally regenerated LV muscle after MI have not been thoroughly examined. Because MI injury significantly disrupts global tissue architecture 15 , confirmation is needed that the regenerated cardiac muscle is mechanically integrated such that tissue-level biomechanical properties are optimally maintained 23 . A previous study employed a cryoinjury model in adult zebrafish, and demonstrated using micropipette aspiration that while the injured myocardium stiffened acutely after sustaining damage, myocardial biomechanics fully normalized by 5 weeks after injury in association with complete natural cardiac regeneration 24 .…”
mentioning
confidence: 99%